2022
DOI: 10.1002/er.7749
|View full text |Cite
|
Sign up to set email alerts
|

Roadmap toward energy‐positive upfront nitrogen removal process in baseload LNG plant

Abstract: Summary The use of liquefied natural gas (LNG) has grown over the last decade owing to an increase in the global energy demand. This work presents a pioneering approach for rigorous simulation of an actual cold section of an LNG plant and provides a potential process optimization to achieve a higher production rate (PR) while reducing the specific power consumption (SPC). The concept of upfront nitrogen removal (UNrem) from the natural gas (NG) feed was introduced, and the impact on the PR and SPC was presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Mkacher et al 85 conducted a thorough experiment in which LNG optimization for cost PSO was performed. In the seven experimental scenarios there was a corresponding UNR of 12.5%, 25%, 37.5%, 50%, 62.5%, 75%, and 87.5%.…”
Section: Economic Considerationsmentioning
confidence: 99%
“…Mkacher et al 85 conducted a thorough experiment in which LNG optimization for cost PSO was performed. In the seven experimental scenarios there was a corresponding UNR of 12.5%, 25%, 37.5%, 50%, 62.5%, 75%, and 87.5%.…”
Section: Economic Considerationsmentioning
confidence: 99%
“…65,67−71 Several studies have shown that the PSO approach is particularly effective. 47,59,70,72 It keeps track of a growing swarm (population) of viable candidate solutions that improve with each iteration as more particles are added. PSO, unlike other heuristic approaches, does not require variable coding or decoding, as it has fewer user-defined tuning parameters, uses fewer variables, and produces faster and better results.…”
Section: ■ Optimization Algorithmmentioning
confidence: 99%
“…Simulation-based optimization (SBO) frameworks using metaheuristic solvers such as simulated annealing (SA), particle swarm optimization (PSO), or genetic algorithm (GA) are commonly used. , Several studies have shown that the PSO approach is particularly effective. ,,, It keeps track of a growing swarm (population) of viable candidate solutions that improve with each iteration as more particles are added. PSO, unlike other heuristic approaches, does not require variable coding or decoding, as it has fewer user-defined tuning parameters, uses fewer variables, and produces faster and better results. …”
Section: Optimization Algorithmmentioning
confidence: 99%